Modified anterior maxillary distraction using "Winged Osteotomy": A technical note - Srinivas Gosla Reddy; Adity Bansal; Nisha Sharma; Ashi Chug (Elsevier, 2021)
Hypoplasia of the maxilla is common in cleft lip and palate (CLP) deformities. Orthognathic surgery has been the traditional method of correction in such developmental anomalies since 1970's, with Le-Fort I advancement as its long-established management modality, which results in significant speech alteration and relapse rate. In contrast, anterior maxillary distraction (AMD) has the advantage of lesser chances of relapse, velopharyngeal insufficiency, and alteration of speech. This modified AMD technique carries a handful of its advantages as it is an easier procedure compared to the Le-Fort I osteotomy as it gives positive soft tissue changes by improving the projection of the nose and the upper lip, normalizes naso-labial angle, and changes the facial prominence from concave to convex simultaneously as it gives nasolabial and sub-malar prominence post-operatively due to the extension of horizontal cuts up to to the zygomatic region, leading to lesser complications. Also, the hollowing caused by the conventional AMD osteotomy cuts is eliminated by the extension of the winged osteotomy.